Simulation Study on Fire Visibility of Typical Floor Planes of Modern Super High-Rise Office Buildings in China. (28th December 2020) - Zhang, Tongtong
Abstract : With the development of office forms, the space form of super high-rise office buildings changed from the unitary efficient office space to a complex space that integrated office, communication, and experience, which also diversified the design of typical floors in the office zone. However, from the perspective of fire prevention, the placement of shared space changed the form of the plane in typical floors in the office zone, affecting the smoke spreading of fire and paths of personnel evacuation. Hence, the subject on the planar relationship among high-rise office buildings based on fire prevention analysis, which optimizes space design, is worthy of discussion. After collecting many cases of super high-rise office buildings in China, this study categorized them into six typical planes and adopted the software PyroSim for comparative simulation of the smoke spreading of fire. By comparing the visibility of different zones in fires, this study analyzed the effects of the area of the office zone, the location of the atrium, and the form of the plane on the fire visibility on the typical floor and put forth the key factors that influence fire visibility, thus optimizing the plane design of the typical floor of super high-rise buildings. The findings show that in the six fire scenes, the area of the office zone is between 1136m 2 and 1736m 2 . The peak of duration for visibility decline at 1.5 m appeared in Scene 3. Its office zone is 1536m 2, and the duration of visibility decline is greater than 1000 s. In other fire scenes, the duration of visibility decline is less than 300 s. By comparing the plane arrangement features of the fire scenes, the paper concludes that in a given fire scene, establishing an atrium in the office zone, expanding the length of the adjacent edge between the atrium and the office zone, and building an evacuation corridor between the atrium and the core tube can greatly extend the effective evacuation time. This can serve as reference for the plane design of super high-rise office buildings.